"The eyes and ears of the agricultural markets": A history of information in interwar agricultural economics - Thomas Delcey; Guillaume Noblet (Duke University, Center for the History of Political Economy (CHOPE), 2021)
This article offers a historical analysis of the contributions of U.S. interwar agricultural economics to the economics of information. Concerned with improving the circulation of information on agricultural markets, agricultural economists analyzed the relationship between agents' information and the behavior of prices on agricultural commodity exchanges, thus anticipating modern debates on informational efficiency. We show that these debates were part of a more general context of agricultural market reform led by the U.S. administration to improve the production and diffusion of economic information. We argue that such reforms were a prerequisite for theoretical discussions on information, and established institutional tools that are still active today, such as the USDA market news service.
Keywords: 330